(1393) government policies and the labour market in Egypt السياسات الحكومية وسوق العمل في مصر - korayem, karima (The Institute Of National Planning., 2018)
The objective of this paper is twofold. First, to find out the government policies that have had an impact on the la-bur market ; and second , to examine these impacts by analyzing the development in the levels and Structures employment, employment and wages in Egypt.